Autophagy inducers restore impaired autophagy, reduce apoptosis, and attenuate blunted alveolarization in hyperoxia‐exposed newborn rats. Issue 8 (12th June 2018) - Zhang, Dan; Wu, Linlin; Du, Yanna; Zhu, Yuting; Pan, Bingting; Xue, Xindong; Fu, Jianhua
Abstract: Aim: Autophagy is a common process during development. Abnormal autophagy can impact cell apoptosis. Previous studies have shown that apoptosis is present during bronchopulmonary dysplasia (BPD). However, there is no consensus on the level of coexisting autophagy. This study was designed to investigate the role of autophagy and the effects of autophagy inducers in a BPD model. Method: A total of 100 newborn Sprague‐Dawley rats were randomly assigned to model and control groups. BPD models were established by hyperoxic induction(FiO2 0.80). Some of them were treated with autophagy‐inducing agents. Result: As compared to the control group, more autophagic bodies were found within Type II alveolar epithelial cells (AT‐II cells) under transmission electron microscopy (TEM) in the model group at 3 d . These autophagic bodies were also accompanied by apoptotic bodies and expression of both bodies peaked at 7 d. As shown by TdT‐mediated dUTP nick end labeling (TUNEL), there were more apoptotic cells in the model group than in the control group. Protein expression levels of LC3B‐II, p62, Lamp1, and cleaved Caspase‐3 increased with increased hyperoxic exposure time. No significant differences were observed in the mRNA expression levels of LC3B, p62, and Lamp1. After introducing an autophagy inducer, either rapamycin or lithium chloride, the radial alveolar count (RAC) value of BPD model group increased as compared with placebo group, the thickness of alveolar septum decreased, while apoptosis decreased. Conclusion: Reduced autophagy resulting from blocked autophagy flow may be a key link in the pathogenesis of BPD. By enhancing repressed autophagy, apoptosis could be reduced and alveolar development improved.